2020
DOI: 10.1002/ejoc.202001098
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Carbide: Versatile Synthetic Applications, Green Methodology and Sustainability

Abstract: Acetylene is a key building block for organic chemistry and potentially can be involved in a diverse range of synthetic transformations. However, critical analysis of practical considerations showed that application of gaseous acetylene in regular synthetic labs encounters a number of difficulties. Safety limitations due to flammable and explosive nature of gaseous acetylene and requirements for specialized high‐pressure equipment impose serious drawbacks. Typical reaction conditions involve excess of gaseous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 109 publications
(83 reference statements)
0
24
0
Order By: Relevance
“…The construction of closed carbon-neutral cycles [10], including the stages of synthesis, application, utilization, and regeneration of carbon-containing molecules, has a fundamentally important role [11]. We previously showed that the conceptual possibility of constructing closed carbon-neutral cycles is provided by atom-economical addition reactions based on calcium carbide (Scheme 1) [12]. Calcium carbide can be obtained by cyclic technology using lime (calcium carbonate and calcium oxide) and various sources of elemental carbon (regenerated carbon, bioderived carbon, coke, charcoal, anthracite, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The construction of closed carbon-neutral cycles [10], including the stages of synthesis, application, utilization, and regeneration of carbon-containing molecules, has a fundamentally important role [11]. We previously showed that the conceptual possibility of constructing closed carbon-neutral cycles is provided by atom-economical addition reactions based on calcium carbide (Scheme 1) [12]. Calcium carbide can be obtained by cyclic technology using lime (calcium carbonate and calcium oxide) and various sources of elemental carbon (regenerated carbon, bioderived carbon, coke, charcoal, anthracite, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Calcium carbide can be obtained by cyclic technology using lime (calcium carbonate and calcium oxide) and various sources of elemental carbon (regenerated carbon, bioderived carbon, coke, charcoal, anthracite, etc.) [12,13]. Acetylene, the simplest alkyne, released during hydrolysis is a molecule of choice for a sequence of atom-economic addition reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach developed here is based on two key components: the use of on-demand production of gas from a suitable precursor and the design of the reactor using 3D printing. The precursor for acetylene is calcium carbide, powerful potential of which has recently been studied through a series of chemical transformations, where acetylene is formed by the addition of water [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. However, the presence of calcium carbide, water, and calcium hydroxide (a side product) is not compatible with a large number of water- or base-sensitive chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…A method for the in situ generation of a D 2 ‐labeled building block, dideuteroacetylene, from calcium carbide and deuterium oxide has been reported recently [3d–h] . Several procedures for the synthesis of specific classes of deuterated compounds from in situ generated C 2 D 2 have been developed.…”
Section: Introductionmentioning
confidence: 99%